Impact of ocean connectedness, environmental identity, emotions, and ocean activities on pro-environmental behaviors - O'Halloran, Chris (Frontiers in Ocean Sustainability, 2025)
This study investigates the association between ocean connectedness, environmental identity, emotions, and experiences with the ocean, and individuals' engagement in pro-environmental behaviors. The data from a total of 1,138 U.S. adults, standardized for age, sex, and regional location, were collected using an online survey. The results revealed ocean connectedness, environmental identity, positive emotions (happiness, gratitude, beauty, awe, joy), as well as select ocean activities (surfing and fishing) are strong predictors of individuals' engagement in pro-environmental behaviors. These findings highlight that designing ocean conservation campaigns and educational programs that leverage emotional engagement and outdoor experiences could be a key strategy to promote ocean conservation and engagement in sustainable actions. Further research is needed to confirm these relationships across different populations and environments.